Agent-based simulation of electricity markets: a literature review - Frank Sensfuß; Mario Ragwitz; Massimo Genoese; Dominik Möst (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2007)
Liberalisation, climate policy and promotion of renewable energy are challenges to players of the electricity sector in many countries. Policy makers have to consider issues like market power, bounded rationality of players and the appearance of fluctuating energy sources in order to provide adequate legislation. Furthermore the interactions between markets and environmental policy instruments become an issue of increasing importance. A promising approach for the scientific analysis of these developments is the field of agent-based simulation. The goal of this article is to provide an overview of the current work applying this methodology to the analysis of electricity markets.
urn:nbn:de:0011-n-661574
Keywords: 330; Elektrizitätswirtschaft; Markteffizienz; Agent-based Model; Simulation